RESTONED. From Waste Material to Sustainable Stone - Annalisa Di Roma; Alessandra Scarcelli; Vincenzo Minenna (Agathón)
The ReSTONED research investigates the theme of environmental sustainability related to the production cycle, starting with the reuse of the stone waste material, to be transformed into new material for indoor and outdoor products. The research is based on the product innovation field, with particular reference to materials from natural sources and furniture. With a view to strengthening the regional circular economy, the research hypothesis is that the production waste, defined as ‘processing mud’, can be re-processed in order to obtain new material with renewed characteristics both from a technical and an aesthetic point of view.